Structural and Chemical Changes to CH3NH3PbI3 Induced by Electron and Gallium Ion Beams. Issue 25 (26th April 2018) - Rothmann, Mathias Uller; Li, Wei; Zhu, Ye; Liu, Amelia; Ku, Zhiliang; Bach, Udo; Etheridge, Joanne; Cheng, Yi‐Bing
Abstract: Organic–inorganic hybrid perovskites, such as CH3 NH3 PbI3, have shown highly promising photovoltaic performance. Electron microscopy (EM) is a powerful tool for studying the crystallography, morphology, interfaces, lattice defects, composition, and charge carrier collection and recombination properties at the nanoscale. Here, the sensitivity of CH3 NH3 PbI3 to electron beam irradiation is examined. CH3 NH3 PbI3 undergoes continuous structural and compositional changes with increasing electron dose, with the total dose, rather than dose rate, being the key operative parameter. Importantly, the first structural change is subtle and easily missed and occurs after an electron dose significantly smaller than that typically applied in conventional EM techniques. The electron dose conditions under which these structural changes occur are identified. With appropriate dose‐minimization techniques, electron diffraction patterns can be obtained from pristine material consistent with the tetragonal CH3 NH3 PbI3 phases determined by X‐ray diffraction. Radiation damage incurred at liquid nitrogen temperatures and using Ga + irradiation in a focused ion beam instrument are also examined. Finally, some simple guidelines for how to minimize electron‐beam‐induced artifacts when using EM to study hybrid perovskite materials are provided. Abstract : Electron and gallium beams rapidly and significantly change the structure and chemical composition of CH3 NH3 PbI3 . Understanding these limitations enables unambiguous study of the atomic structure and microstructures of hybrid perovskites.